RNA-binding proteins contribute to small RNA loading in plant extracellular vesicles - He, Baoye (Nat Plants, 2021)
Plants utilize extracellular vesicles (EVs) to transport small RNAs (sRNAs) into their fungal pathogens and silence fungal virulence-related genes through a phenomenon called “cross-kingdom RNAi.” It remains unknown, however, how sRNAs are selectively loaded into EVs. Here, we identified several RNA-binding proteins (RBPs) in Arabidopsis, including Argonaute 1 (AGO1), RNA helicases (RHs) and Annexins (ANN), which are secreted by exosome-like EVs. AGO1, RH11 and RH37 selectively bind to EV-enriched sRNAs but not non-EV enriched sRNAs, suggesting that they contribute to the selective loading of sRNAs into EVs. Conversely, ANN1 and ANN2 bind to sRNAs non-specifically. The ago1, rh11rh37 and ann1ann2 mutants showed reduced secretion of sRNAs in EVs, demonstrating that these RBPs play an important role in sRNA loading and/or stabilization in EVs. Furthermore, rh11rh37 and ann1ann2 showed increased susceptibility to Botrytis cinerea, supporting that RH11, RH37, ANN1 and ANN2 positively regulate plant immunity against B. cinerea.